Residue Depletion Profile and Estimation of Withdrawal Period for Sulfadimethoxine and Ormetoprim in Edible Tissues of Nile Tilapia (Oreochromis sp.) on Medicated Feed - de Freitas, Lucas Victor Pereira; da Mota Júnior, Carlos Augusto Alvarenga; Damaceno, Marina Alves; Silveira, Juliana Grell Fernandes; Portela, Ana Carolina Vellosa; Campanharo, Sarah Chagas; da Silva, Agnaldo Fernando Baldo; Assane, Inácio Mateus [UNESP]; Pilarski, Fabiana [UNESP]; Sasanya, James Jacob; Paschoal, Jonas Augusto Rizzato (MDPI, 2023)
Sulfadimethoxine (SDM) and ormetoprim (OMP) are antimicrobials used in combination to treat bacterial infections in fish farming. The use of this drug combination is not yet regulated in some countries, such as Brazil. Due to the lack of regulated drugs for aquaculture in Brazil, this study investigated the residue depletion profile of SDM and OMP in Nile tilapia (Oreochromis sp.) after oral administration. Fish were treated with medicated feed containing a 5:1 ratio of SDM:OMP at the dose of 50 mg kg BW−1 for five consecutive days with an average water temperature of 28 °C. The drugs were incorporated into the feed by using a gelatin coating process which promoted homogeneity in drug concentration and prevented the drug leaching into the water during medication. The SDM and OMP determination in fish fillets (muscle plus skin in natural proportions) was performed using the QuEChERS approach followed by LC-MS/MS quantification. The analytical method was validated according to Brazilian and selected international guidelines. A withdrawal period of 9 days (or 252 °C days) was estimated for the sum of SDM and OMP residues at concentration levels below the maximum residue level of 100 µg kg−1.
Keywords: aquaculture; food safety; LC-MS/MS; QuEChERS; tilapia; veterinary drug residues; withdrawal period